2017
DOI: 10.1177/0954410017717546
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation control on a highly loaded compressor cascade using endwall synthetic jets

Abstract: This paper presents flow separation control conducted on a highly loaded compressor stator cascade using endwall synthetic jets. Numerical methods are employed and mechanisms of endwall synthetic jets in improving the cascade performance are discussed in detail. The influence of several actuation parameters is also investigated. Results show that endwall synthetic jets are able to improve the flows in the blade passage significantly, a maximum loss reduction of 21.63% and a pressure rise increment of 5.60% are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Seifert et al [15] applied the jet actuator to an aerofoil, and the aerodynamic performance of the aerofoil was improved obviously. Qin et al [16] used end wall SJ to control the flow separation of stator cascade of high-load compressor. The results showed that the end wall SJ can significantly improve the flow in the blade channel.…”
Section: Introductionmentioning
confidence: 99%
“…Seifert et al [15] applied the jet actuator to an aerofoil, and the aerodynamic performance of the aerofoil was improved obviously. Qin et al [16] used end wall SJ to control the flow separation of stator cascade of high-load compressor. The results showed that the end wall SJ can significantly improve the flow in the blade channel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the flow separation was improved, and 21.63% reduction of the losses was achieved. 15 The magnitude of the mass flow rate of the tip-jets is larger than that of the jets used for flow control. The tip-jets flow phenomenon of expansion, dissipation, and entrainment is developed inside the ducted fan.…”
Section: Introductionmentioning
confidence: 99%